Quantifying the Influence of Out-Time on Prepreg Material Properties and Out-Of-Plane Steering Defects During Automated Fiber Placement - Heller, Klaus; Colin, David; Drechsler, Klaus (Frontiers in Materials, 2022)
In automated fiber placement (AFP), knowledge about the interaction between material properties and process parameters is essential to achieve cost-efficient manufacturing. Both, lay-up rate and defects are dependent on the properties of the uncured prepreg tapes which are out time dependent. However, information thereof is not given in data sheets and there are no standardized test methods. To quantify the changes of the material properties, we conducted experiments on mechanical properties and tack with IM7/8552 up to 15 d out time using previously evaluated test methods. Furthermore, we carried out AFP lay-up trials to quantify the effects on steering defects. The results for the mechanical properties reveal a non-linear increase of the shear modulus and the transverse tensile modulus and a strong correlation to the test temperature. Results from the probe tack tests show a strong dependence on out time at 20 °C and a weak dependence at 40 °C. Results from a novel peel tack test method and the lay up trials revealed a monotonous change as a function of out time. In both cases, we identified the lay up rate and the infrared (IR) emitter power as the process parameters with the largest influence. The obtained results present an overall view of the material behavior depending on different test and process parameters as a function of out time. By this, they help optimize the AFP process parameters and serve as input for material models and AFP defect models.